2015
DOI: 10.1007/s12630-015-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors for acute kidney injury after liver resection surgery: an historical cohort study

Abstract: Perioperative risk factors for AKI after liver resection surgery are similar to those established for other surgical procedures. Further studies are needed to establish causality and to determine whether interventions on modifiable risk factors can reduce the incidence of postoperative AKI and improve patient outcome. This study was registered at the University Hospital Medical Information Network (UMIN) Center (UMIN 000008089).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 43 publications
4
54
0
1
Order By: Relevance
“…Perioperative haemorrhage with renal hypoperfusion[6], with or without the deleterious effects of blood transfusion[3], was a strong predictor of postoperative AKI in this study, reflected by intraoperative hemodynamic instability and posthepatectomy haemorrhage. An increased renal susceptibility to the perioperative renal ischemia[22-25], such as in CKI, was a predictor in the authors’ series.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Perioperative haemorrhage with renal hypoperfusion[6], with or without the deleterious effects of blood transfusion[3], was a strong predictor of postoperative AKI in this study, reflected by intraoperative hemodynamic instability and posthepatectomy haemorrhage. An increased renal susceptibility to the perioperative renal ischemia[22-25], such as in CKI, was a predictor in the authors’ series.…”
Section: Discussionmentioning
confidence: 89%
“…Eventually, patients can have combinations of renal insults that can be aggravated by sepsis[2,3,5,6], which was an independent predictor in the authors’ analysis. The septicemia and its hemodynamic and systemic repercussions may eventually coexist with liver failure, often being the final event of PHLF[5].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Blood loss and transfusions are associated with morbidity in hepatectomy patients , but we were limited by the fact that the dataset only indicates if blood was administered within the first 72 h of surgery. Our goal was to create a risk score that could be applied immediately after surgery so this variable was not included in the multivariable analysis, but a sensitivity analysis demonstrated that intra/postoperative transfusions would have been an additional significant risk factor for postoperative AKI in our model (data not shown).…”
Section: Discussionmentioning
confidence: 99%